Shear Performance of Damaged Concrete Beams Reinforced by Penetrating FRP. Issue 1 (September 2020) - Jiang, Tianhua; Yu, Yi; Yu, Yalu; Zhang, Xiucheng; Huang, Wen
Abstract: This experimental study examined the shear behavior of damaged concrete beams reinforced with fiber-reinforced polymer (FRP) using a penetration method (penetration FRP) to explore the failure modes of the reinforced beams. The load-displacement curves and load-strain curves of the samples were analyzed, and the development and distribution of the oblique cracks of the reinforced beams were discussed. The influences of the damage degree and the reinforcement angle on the shear bearing capacity were determined. The results showed that, prior to cracking, FRP reinforcement had no effect on the stiffness of the samples and the cracking load of the samples remained basically the same; however, after cracking, the samples reinforced with FRP exhibited a larger shear capacity. Moreover, the ultimate load was higher for the undamaged reinforced beam than the damaged reinforced beam. The penetration of the FRP material into the beam at an oblique angle inhibited the development of oblique cracks, resulting in a better reinforcement effect and optimal bearing capacity of the strengthened beam.